1986
DOI: 10.1016/0014-5793(86)80750-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a novel glycolipid, 'trehalose 2,3,6'‐trimycolate' in a psychrophilic, acid‐fast bacterium, Rhodococcus aurantiacus (Gordona aurantiaca)

Abstract: A new type of glycolipid possessing trehalose and mycolic acids has been identified in the lipids of Rhodococcus aurantiacus (Gordona aurantiaca), a psychrophilic acid-fast bacterium. Gas chromatographic and gas chromatographic-mass spectrometric analysis of hydrolysis products of the most abundant glycolipid class (GM) (containing approx. 50% of the total lipids) showed that the hydrophilic moiety was composed essentially of trehalose, while the hydrophobic moiety contained Chr-74 polyunsaturated mycolic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Strains identified as "Streptomyces candidus" from the purulent exudate of a fractured patella, "Streptomyces gedaensis" from sputum and abscesses, "Streptomyces horton" from pus, and "Streptomyces willmorei" from streptothricosis of the liver have also been reported (316). The (205,467,589,590). It was first discovered in humans in 1971 by Tsukamura closely related to T. paurometabola; however, the members of the genomic species of T wratislaviensis have DNA that is less rich in guanine plus cytosine than the DNA of the members of the genomic species of T. paurometabola.…”
Section: Opportunistic Pathogenic Actinomycetesmentioning
confidence: 99%
“…Strains identified as "Streptomyces candidus" from the purulent exudate of a fractured patella, "Streptomyces gedaensis" from sputum and abscesses, "Streptomyces horton" from pus, and "Streptomyces willmorei" from streptothricosis of the liver have also been reported (316). The (205,467,589,590). It was first discovered in humans in 1971 by Tsukamura closely related to T. paurometabola; however, the members of the genomic species of T wratislaviensis have DNA that is less rich in guanine plus cytosine than the DNA of the members of the genomic species of T. paurometabola.…”
Section: Opportunistic Pathogenic Actinomycetesmentioning
confidence: 99%
“…These mycoloyl residues are attached to 2, 3, and 6' position of trehalose (25). We have also shown that this unique glycolipid possessed a potent granuloma-forming activity in lungs and spleen of mice, when administered in liposomes intravenously (30).…”
mentioning
confidence: 76%
“…According to our previous paper (25), G. aurantiaca strain 80005 (provided by Dr. M. Tsukamura, National Sanatorium Chubu Hospital) was cultivated at 30 C, aerobically for 7 days in a medium containing 1 % glucose, 0.5% peptone, and 0.2% yeast extract. Cells were harvested and the lipids were extracted with chloroform/methanol (2 :1, v/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trehalose is also found in a variety of actinomycetes and related bacteria including species of the genera Streptomyces, Nocardia, Mycobacterium, and Corynebacterium (13); Frankia (25); Micromonospora (11); Arthrobacter (33); Cellulomonas (29); Micrococcus (1); Microbacterium (37); Bacterionema (30); Propionibacterium (31); and Rhodococcus (35). Trehalose accumulation appears to be characteristic of these bacteria.…”
Section: Discussionmentioning
confidence: 99%